Twinkling effect in detecting kidney stone - Lim, Ee Wei. (2012)
Kidney stone is a common urologic disease but ultrasound diagnosis of kidney stone is usually not easy because of the bad image quality. The “twinkling artefact” is a useful tool in diagnosing the kidney stone as well as for better tissue characterisation. This artefact is being described as a rapidly alternating red and blue Doppler signal generated by strongly reflective medium. Studies have shown that the artefact is dependent on the characteristics of the interface and inner geometric arrangement of the kidney stones. However the artefact is not consistent behind the calcification. This project aims to study the relations between the Doppler sonography and physical mechanisms of phantoms.